Perancangan Sistem Informasi Evaluasi Kinerja Guru Berbasis Website Menggunakan Soft System Methodology (SSM) (Studi Kasus di SMK Taruna Tama Getasan) - Sinulingga, Yedija Sada Ukurta; Hartomo, Kristoko Dwi (Jurusan Teknologi Informasi Universitas Semarang, 2021)
Performance assessment system is a reference of school to determine the performance quality of a teacher that also a reference to determine their career development and career promotion. The teacher has to improve their skills and ability to apply the competence to improve the quality of the learning process. The expansion of performance assessment information system in SMK Taruna Tama Getasan Salatiga will help the assessor to make performance assessment report because the previous method they used conventional system that hinder the process of the rating like a difficult calculation and take so much time. This system use Soft System Methodology (SSM) by using structured approach to understand some issues, build conceptual mode, get eligibility and the implementation. System testing use Webqual 4.0 and using 3 (three) instruments are Usability Quality, Information Quality and Service Interaction Quality. By using 122 that processed by SPSS software which testing the validity test, reliability and linear regression correlation. From the test result that the website of performance assessment system are having a good quality based on Usability Quality, Information Quality and Service Interaction Quality.